Minimum virgin binder limits in recycled Superpave (SR) mixes in Kansas - Tavakol, Masoumeh (Kansas State University, 2016)
Use of recycled materials in asphalt pavement has become widespread recently due to rising costs of virgin binder and increased attention to sustainability. Historically, recycled asphalt pavement (RAP) has been the most commonly used recycled material for hot-mix asphalt (HMA). However, recycled asphalt shingle (RAS), another recycled material, has recently become popular. Although there are some guidelines regarding use of RAP and RAS in HMA, their effects on mixture performance, especially on mixtures containing RAS, are not thoroughly understood. In this research, three recycled Superpave mixture designs from the Kansas Department of Transportation (KDOT) with 9.5 mm (SR-9.5A) and 19 mm (SR-19A) Nominal Maximum Aggregate Size (NMAS) were selected as control mixtures. Mixtures containing higher percentages of recycled materials (RAP and RAS) were developed using KDOT blending charts. A total of nine mixtures with varying virgin binder contents were designed and assessed for moisture susceptibility, rutting resistance, and fatigue cracking propensity using modified Lottman, Hamburg Wheel Tracking Device, flow number, Dynamic Modulus, and S-VECD direct tension fatigue tests. Results confirmed the effect of NMAS and material source on mixture performance. For SR-9.5A, the mixtures showed increased susceptibility to moisture and rutting damage below virgin binder content of 75%. For SR-19A, mixtures with virgin binder content of 70% showed satisfactory performance properties. Mixtures with virgin binder contents lower than 60% definitely showed inferior performance.
Keywords: RAP; RAS; Hot-Mix Asphalt; Recycled Superpave Mixture; Mixture Performance Properties